An Analysis of Main Character in the Book “Bawang Merah and Bawang Putih” - Ni Luh Komang Puspa Dewi; I Gusti Ayu Mahatma Agung (LPPM Universitas Bumigora Mataram, 2023)
Folk tales can be used as a media to teach moral values ​​to children. Folk tale is told from generation to generation through oral tradition. Since it is conveyed orally, several versions of the folk tale are sometimes found in society. This study aims to find out the differences in plot and characterization in the two versions of the folk tale“Bawang Merah dan Bawang Putih”. The descriptive qualitative method was applied in this study. The researchers analyzed the characters and plots in two folk tale books entitled “Bawang Merah dan Bawang Putih” and “Bawang dan Kesuna”. The data of characterization was classified and analyzed using the theory proposed by Mays (2018). Based on the analysis, the results showed that there were three differences in the characterization, namely differences in family relations, differences in parental behavior, and differences in personality. Furthermore, there were also differences found in the plot, namely unfortunate events, unexpected gifts, evil ideas, and sad endings.